Studi Fenomenologi Model Implementasi CSR Berkelanjutan Di Kampung Warna-Warni Jodipan - Erif Nurhuda; Satia Nur Maharani; Ridoni Fardeni Harahap (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2021)
Effective implementation of CSR programs is expected to provide long-term bene-fits and is continuous. The purpose of this research is to formulate a model for im-plementing a sustainable CSR program. This study uses a descriptive method with a qualitative transcendental phenomenological approach that aims to, obtain in-depth and pure information from the object of research related to the implementa-tion model of sustainable CSR programs. The results of this study show the imple-mentation model of sustainable CSR programs that continuously provide benefits to the community and the company. Building a sustainable CSR program is carried out through the implementation of appropriate programs against targets and tar-gets, directed at community problems. The alignment of the program model given with problems in the community and can touch the root of these problems directly. He considered every triple bottom line element in the program implementation. The sustainability of the CSR program indirectly involves the active participation of the community and the company carries out a series of directed, systematic and planned management activities. Moreover, sustainable CSR programs cannot be separated from interference or support from the government and universities.